A New Classification of Anterior Choroidal Artery Aneurysms and Its Clinical Application - Duan, Yu; Qin, Xuanfeng; An, Qinqzhu; Liu, Yikui; Li, Jian; Chen, Gong (Frontiers in Aging Neuroscience, 2021)
Background and Purpose: The aim of this study was to compare the different subtypes of anterior choroidal artery (AChoA) aneurysm based on a new classification and to analyze the risk factors according to individual endovascular treatment (EVT). Methods: In the new classification, AChoA aneurysms are classified into independent type (I type) and dependent type (II type) based on the relationship between the AChoA and the aneurysm. II type aneurysms have three subtypes, IIa (neck), IIb (body), and IIc (direct). We retrospectively analyzed 52 cases of AChoA aneurysm treated in our center between 2015 to 2019. There were 13 (25.0%) I type aneurysms, 24 (46.2%) IIa aneurysms, 15 (28.8%) IIb aneurysms, and no IIc type; 28 cases had a subarachnoid hemorrhage. According to our preoperative EVT plan for the different subtypes: II type should achieve Raymond-Roy Occlusion Class 1 (RROC 1) where possible. To protect the AChoA, it is best to preserve the neck of the IIa type aneurysms (RROC 2), and RROC 3 is enough for IIb type. Results: Ten asymptomatic cases with minimal aneurysms were treated conservatively. Of the other cases, 42 were treated with individualized EVT (26 with a simple coil, 6 with balloon-assisted coiling, 7 with stent-assisted coiling, and 3 by flow diverter. Different subtypes had different RROC (Z = 14.026, P = 0.001). IIb type aneurysms (χ2 = 7.54, P = 0.023) were one of the factors related to temporary or permanent AChoA injury during surgery. Overall, two patients (IIa = 1, IIb = 1) developed contralateral hemiparesis. Conclusions: The new classification diagram clearly shows the features of all types of AChoA aneurysm and makes EVT planning more explicit. The II type (particularly IIb) was a potential risk factor for AChoA injury.